Practical considerations for bicarbonate loading and sports performance - Burke, L. M. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Consumption of sodium bicarbonate (300 mg/kg 1-2 h before exercise) can temporarily increase blood bicarbonate concentrations, enhancing extracellular buffering of hydrogen ions which accumulate and efflux from the working muscle. Such `bicarbonate loading' provides an ergogenic strategy for sporting events involving high rates of anaerobic glycolysis which are otherwise limited by the body's capacity to manage the progressive increase in intracellular acidity. Studies show that bicarbonate loading strategies have a moderate positive effect on the performance of sports involving 1-7 min of sustained strenuous exercise, and may also be useful for prolonged sports involving intermittent or sustained periods of high-intensity work rates. This potential to enhance sports performance requires further investigation using appropriate research design, but may be limited by practical considerations such as gut discomfort or the logistics of the event. The effect of chronic use of bicarbonate supplementation prior to high-intensity workouts to promote better training performance and adaptations is worthy of further investigation. While this relatively simple dietary strategy has been studied and used by sports people for over 80 years, it is likely that there are still ways in which further benefits from bicarbonate supplementation can be developed and individualized for specific athletes or specific events.